2017
DOI: 10.1128/jvi.02411-16
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-Dependent RNA Helicase DDX3X Modulates Herpes Simplex Virus 1 Gene Expression

Abstract: The human protein DDX3X is a DEAD box ATP-dependent RNA helicase that regulates transcription, mRNA maturation, and mRNA export and translation. DDX3X concomitantly modulates the replication of several RNA viruses and promotes innate immunity. We previously showed that herpes simplex virus 1 (HSV-1), a human DNA virus, incorporates DDX3X into its mature particles and that DDX3X is required for optimal HSV-1 infectivity. Here, we show that viral gene expression, replication, and propagation depend on optimal DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…Depletion of VP16 or VP22 in virions hints at a complex scenario. To orthogonally confirm our findings, we used an RNA interference strategy to lower the amounts of the proteins in the virions and assessed their infectivity, an approach we successfully used in the past for VP16 and several host proteins incorporated in virions (13,26). As anticipated, short interfering RNA (siRNA) targeting VP16 or VP22 significantly reduced the level of expression of these proteins in infected cell lysates (Fig.…”
Section: Figsupporting
confidence: 66%
“…Depletion of VP16 or VP22 in virions hints at a complex scenario. To orthogonally confirm our findings, we used an RNA interference strategy to lower the amounts of the proteins in the virions and assessed their infectivity, an approach we successfully used in the past for VP16 and several host proteins incorporated in virions (13,26). As anticipated, short interfering RNA (siRNA) targeting VP16 or VP22 significantly reduced the level of expression of these proteins in infected cell lysates (Fig.…”
Section: Figsupporting
confidence: 66%
“…Thus, removing the region interferes with protein expression . This hypothesis would also be consistent with the stimulation of HSV TK gene expression by the cellular RNA helicase DDX3X . These assumptions are not in contradiction to the lack of reactivity of the LS +5/+15 mutant in HSV‐infected mouse L cells as the study only looked at TK mRNA not the protein levels .…”
Section: Resultssupporting
confidence: 61%
“…Thus, proteins binding to the region +5 to +15 of the 5 0 -UTR-coding DNA might not be important for the regulation of HSV TK expression. Recently, it was shown that the cellular RNA helicase DDX3X is important for the regulation of HSV early genes including UL23, which encodes for HSV TK, suggesting that TK mRNA structures or small RNA may regulate HSV TK gene expression in HSV-infected cells [52]. It is important to note that none of the cell lines studied here expresses ICP4 and the putative factor binding to the region +5 to +27 of the 5 0 -UTR at the DNA or RNA level seems to act as a repressor and not an activator in uninfected mouse and human cells as removing its putative binding site increases protein expression.…”
mentioning
confidence: 99%
“…Wild-type HSV-1 strain 17 ϩ and the HSV-1 (17 ϩ ) Lox-Luc viral strain (both obtained from Beate Sodeik) were propagated on BHK cells, and their titers were determined by plaque assay on Vero cells. The latter virus is derived from strain 17 ϩ and encodes a Gaussian luciferase gene under the constitutively expressed immediate-early cytomegalovirus (CMV) promoter positioned between the UL55 and UL56 HSV-1 genes (57).…”
Section: Methodsmentioning
confidence: 99%